Gentamycin delivered from a PDLLA coating of metallic implants: in vivo and in vitro characterisation for local prophylaxis of implant-related osteomyelitis - Vester, Helen; Wildemann, Britt; Schmidmaier, Gerhard; Stöckle, Ulrich; Lucke, Martin (Injury, 2010)
Locally applied antibiotics support prophylaxis of highly feared implant associated infections. Implant coatings with poly(d,l-lactide) (PDLLA)/gentamicin seem to be a promising approach. Aims of this study were to analyse the release kinetics of gentamicin in vivo, in vitro, to analyse the antibacterial efficacy, the resistance development and its impact on osteoblasts. For the in vitro release experiments titanium implants were coated with PDLLA/gentamicin and the antibiotic release in aqueous solution was analysed at 20 time points (from 10s to 110 days). For the in vivo experiments PDLLA/gentamicin-coated kirschner wires were implanted in the tibiae of 18 rats. Gentamicin concentration in the bone was analysed at several time points (n=3 each, 1h to 7 days). Bactericidal efficacy, bacterial adhesion on the implants and resistance development were tested. AP activity, cell count and CICP expression of osteoblasts were analysed. Gentamicin was released rapidly with an initial burst in aqueous solution and followed by a slow release. Similarly, in vivo gentamicin concentration reached a high peak initially followed by a decrease to a low level. No development of resistance was observed in the investigated setting, the antibacterial efficacy was not affected by the coating process and significantly fewer bacteria were attached to the implant. Osteoblasts were not negatively affected by the gentamicin released from the coating. PDLLA/gentamicin coating resulted in a desired antibiotic peak concentration within the bone. Bacterial adhesion was successfully prevented. No bacterial resistances were developed. This coating seems to be a suitable supplement for prophylaxis of implant-associated infections.